DETERMINANTS OF INDIVIDUALS’ INTENTION IN PATRONIZING WASIYYAH SERVICES IN MALAYSIA - Amalina Mursidi; Khairil Faizal Khairi (Journal of Islamic Management Studies, 2020)
Wasiyyah is one of the most important things that should be aware of before death. This is important in order to ensure the beneficiaries can get their rights after a person dies. The present study investigates the effects of the following factors; attitude, subjective norm and perceived behavioural control on the individual’s intention in patronizing wasiyyah services. The sample of this study consists of 250 respondents and the questionnaires were randomly distributed to Malaysian Muslims in the area of Klang Valley whose age was 25 and above. Data were obtained through an e-mail and face-to-face survey using a semi-structured questionnaire. The result indicates that all three independent variables were significant to influence the individual’s intention in patronizing wasiyyah services. The study found that the subjective norm is the strongest factor in predicting the dependent variable and this result did not support the fourth hypothesis. The respondents also were reluctant to answer the questionnaire due to the lack of knowledge on wasiyyah. Despite these limitations, the findings of this study provide invaluable insights on factors tested in TPB regarding the intentions in patronizing wasiyyah services.